Chromium-zirconium-copper alloy and preparation method thereof
By accurately controlling the content of chromium and zirconium and adopting preheating, melting, purification and homogenization steps, the problem of performance degradation of chromium-zirconium copper alloy due to uneven element distribution is solved, and the hardness, strength, wear resistance and corrosion resistance are improved, and it is suitable for high-end application fields.
Patent Information
- Application Number
- CN202411524375.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-03-04
AI Technical Summary
Traditional copper-zirconium copper alloys have deteriorated performance due to uneven distribution of chromium and zirconium elements during smelting and casting, especially in local areas.
By accurately controlling the content of chromium and zirconium, and using preheating, melting, purification and homogenization, argon is blown in during the process for protection and stirring, ensuring that the components of chromium-zirconium copper alloy are evenly distributed.
It effectively improves the hardness, strength, wear resistance and corrosion resistance of chromium-zirconium copper alloy, while maintaining good conductivity and processing performance, and is suitable for high-end applications.
Smart Images

Figure CN119553131A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of metal alloy manufacturing, and specifically relates to a chromium-zirconium-copper alloy and a preparation method thereof. Background Art
[0002] In the traditional smelting and casting process, the distribution of elements such as chromium and zirconium in the alloy is often not uniform, which will lead to a decrease in the various properties of the prepared chromium-zirconium-copper alloy (such as tensile strength, hardness and toughness), especially the appearance of performance differences in local areas. Summary of the invention
[0003] In view of the deficiencies in the prior art, the purpose of the present application is to provide a chromium-zirconium-copper alloy and a preparation method thereof. The present application aims to solve the problem in the prior art that the chromium-zirconium-copper alloy has poor performance due to the uneven distribution of elements such as chromium and zirconium.
[0004] To achieve the above objectives, this application provides the following technical solutions:
[0005] A chromium-zirconium-copper alloy comprises components and contents of the components: chromium (Cr): 0.5-1.5%, zirconium (Zr): 0.02-0.2%, and copper (Cu): the remainder.
[0006] In addition, the present application also provides a method for preparing a chromium-zirconium-copper alloy, which includes: preheating an electrolytic copper plate; melting the preheated electrolytic copper plate to obtain a copper liquid; covering the surface of the copper liquid with flake graphite to insulate the copper liquid; purifying the insulated copper liquid; dissolving the alloying elements chromium and zirconium in the purified copper liquid; casting and solidifying the copper liquid containing the alloying elements chromium and zirconium to obtain a chromium-zirconium-copper alloy.
[0007] Optionally, the preheating temperature is 300-500°C.
[0008] Optionally, the preheating time is 30-60 minutes.
[0009] Optionally, the melting temperature of the electrolytic copper plate is 1200-1380°C.
[0010] Optionally, the coverage thickness of the flake graphite is 50-150 mm.
[0011] Optionally, the copper liquid is kept warm for 10-30 minutes.
[0012] Optionally, during the purification of the copper liquid after heat preservation, argon gas needs to be blown onto the surface of the copper liquid, and the flow rate of the argon gas is 25-45 L / min.
[0013] Optionally, the casting temperature of the copper liquid in which the alloy elements chromium and zirconium are dissolved is 1280-1300°C.
[0014] In addition, the present application also proposes an alloying crucible, which includes a wire feeding chamber, an overflow chamber and a refining chamber, wherein the wire feeding chamber is used for adding and dissolving the alloying elements chromium and zirconium; the overflow chamber is used for removing impurities generated during the process of adding the alloying elements chromium and zirconium; and the refining chamber is used for refining the copper liquid with the alloying elements chromium and zirconium added.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] The present application can effectively improve the hardness, strength, wear resistance and corrosion resistance of the chromium-zirconium-copper alloy while maintaining good electrical conductivity and processing properties by precisely controlling the content of chromium and zirconium, adopting steps such as preheating, melting, purification and homogenization, and blowing in an appropriate amount of argon gas for protection and stirring during the process, thereby preparing a high-quality chromium-zirconium-copper alloy suitable for high-end application fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic flow chart of a method for preparing a chromium-zirconium-copper alloy provided in one embodiment of the present application;
[0018] Figure 2 is a schematic diagram of the macroscopic metallographic structure of a chromium-zirconium-copper alloy provided in another embodiment of the present application;
[0019] Figure 3 is a schematic diagram of the microstructure of a chromium-zirconium-copper alloy provided in another embodiment of the present application;
[0020] Figure 4 It is a schematic diagram of electron microscope scanning of a chromium-zirconium-copper alloy provided in another embodiment of the present application. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0022] It should be noted that all directional indications in the embodiments of the present application (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0023] In this application, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0024] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present application, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by this application.
[0025] In an exemplary embodiment, the present application provides a chromium-zirconium-copper alloy, wherein the components of the chromium-zirconium-copper alloy and the mass percentage of each component are:
[0026] Chromium (Cr): 0.5-1.5%
[0027] Zirconium (Zr): 0.02-0.2%
[0028] Copper (Cu): balance.
[0029] The present application conducts performance tests such as tensile strength and hardness, corrosion resistance, ductility and toughness, and casting fluidity on chromium-zirconium-copper alloys with different mass percentages. The test results are shown in Tables 1 and 2, wherein Table 1 shows the effect of different chromium (Cr) contents on the performance of chromium-zirconium-copper alloys, and Table 2 shows the effect of different zirconium (Zr) contents on the performance of chromium-zirconium-copper alloys.
[0030] Table 1
[0031]
[0032] It can be seen from Table 1 that with the increase of chromium (Cr) content, the tensile strength of chromium-zirconium-copper alloy gradually increases from 500MPa (0.3% Cr) to 700MPa (1.5% Cr). When the chromium (Cr) content exceeds 1.5%, the tensile strength of chromium-zirconium-copper alloy decreases to 680MPa (1.7% Cr). With the increase of chromium (Cr) content, the hardness of chromium-zirconium-copper alloy increases from 90HB (0.3% Cr) to 130HB (1.5% Cr). Even at 1.7% chromium (Cr), the hardness of chromium-zirconium-copper alloy remains at 130HB. When the chromium (Cr) content is 0.5% or above, the corrosion resistance of chromium-zirconium-copper alloy is significantly improved, and the corrosion area is reduced from 10mm to 130mm. 2 (0.3% Cr) reduced to 0.1mm 2 (0.8% Cr and above). When the chromium (Cr) content is between 0.5-1.5%, the elongation of the chromium-zirconium-copper alloy remains in a reasonable range of 3-4.5%. When the chromium (Cr) content exceeds 1.5%, the elongation of the chromium-zirconium-copper alloy drops to 2.5%, indicating that the chromium-zirconium-copper alloy becomes brittle and hard.
[0033] In summary, when the chromium (Cr) content is controlled between 0.5-1.5%, the chromium-zirconium-copper alloy has high tensile strength, hardness and good corrosion resistance, while maintaining reasonable ductility and toughness. When the chromium (Cr) content is lower than 0.5%, the various properties of the chromium-zirconium-copper alloy are poor; when the chromium (Cr) content exceeds 1.5%, although the hardness and corrosion resistance of the chromium-zirconium-copper alloy are good, the ductility and toughness decrease, which is easy to cause cracking.
[0034] Table 2
[0035]
[0036] In Table 2, regarding the grain refinement effect, as the zirconium (Zr) content increases, the grain size of the chromium-zirconium-copper alloy gradually decreases, from more than 100μm at 0.01% Zr to less than 50μm at 0.2% Zr. Regarding the strength change, when the zirconium (Zr) content is between 0.02-0.2%, the strength of the chromium-zirconium-copper alloy is significantly improved, from +5% (0.01% Zr) to +25% (0.2% Zr). Regarding the elongation, when the zirconium (Zr) content exceeds 0.2%, the strength improvement of the chromium-zirconium-copper alloy is no longer obvious, and it is still +20% (0.3% Zr). Regarding fluidity and casting quality, when the zirconium (Zr) content is between 0.02-0.2%, the elongation of the chromium-zirconium-copper alloy increases from 2.5% to 4.5%. When the zirconium (Zr) content exceeds 0.2%, the elongation of the chromium-zirconium-copper alloy drops to 3%. As the zirconium (Zr) content increases, the fluidity of the chromium-zirconium-copper alloy gradually decreases from 85 (0.01% Zr) to 70 (0.2% Zr). When the zirconium (Zr) content exceeds 0.2%, the fluidity of the chromium-zirconium-copper alloy further decreases to 60 (0.3% Zr). At the same time, the casting defect rate also gradually increases from 0 (0.01% Zr) to 1.5% (0.3% Zr).
[0037] In summary, controlling the zirconium (Zr) content between 0.02-0.2% can effectively refine the grains and is sufficient to improve the strength, toughness and casting fluidity of the chromium-zirconium-copper alloy. If the zirconium content is less than 0.02%, the role of zirconium (Zr) in grain refinement and mechanical property enhancement cannot be fully utilized, resulting in the strength and toughness of the chromium-zirconium-copper alloy not meeting the expected requirements; and if the zirconium (Zr) content is greater than 0.2%, although the grain refinement effect still exists, too much zirconium (Zr) will form more second phase particles (such as Cu-Zr compounds), which will cause the chromium-zirconium-copper alloy to become brittle and reduce its ductility and toughness. In addition, too much zirconium (Zr) will cause the viscosity of the copper liquid to increase and the fluidity to deteriorate. During the casting process, if the fluidity of the copper liquid deteriorates, it is difficult to completely fill the space in the mold or crystal body, resulting in defects such as pores and shrinkage holes inside the chromium-zirconium-copper alloy, thereby affecting the quality and yield of the chromium-zirconium-copper alloy.
[0038] In summary, controlling the chromium (Cr) content between 0.5-1.5% and the zirconium (Zr) content between 0.02-0.2% is an optimized choice. Within this range, the various properties of the chromium-zirconium-copper alloy can be effectively improved, and at the same time, the negative effects caused by excessively high or low zirconium (Cr) and zirconium (Zr) contents can be avoided.
[0039] Figure 1 is a schematic flow chart of a method for preparing a chromium-zirconium-copper alloy provided by an exemplary embodiment of the present application, such as Figure 1As shown, the method includes:
[0040] S1: Preheat the electrolytic copper plate to 300°C for 30 minutes;
[0041] In this step, electrolytic copper plates are used as raw materials for preparing copper liquid, mainly because electrolytic copper plates are produced through an electrolytic refining process, have very high purity, and can be used as ideal raw materials for preparing high-quality chromium-zirconium-copper alloys.
[0042] S2: Melting the preheated electrolytic copper plate in a graphite crucible at a temperature of 1200° C. to obtain copper liquid;
[0043] S3: Covering the surface of the copper liquid with graphite flakes having a thickness of 50 mm, and draining the copper liquid covered with graphite flakes from the crucible to the homogenization chamber for 10 minutes;
[0044] In this step, the flake graphite is a loose and porous material, which can form a physical barrier on the surface of copper liquid. Since copper liquid is very easy to react with oxygen in the air to generate oxide at high temperature, this covering layer can effectively isolate oxygen in the air from contacting with copper liquid, thereby reducing the oxidation of copper liquid. In addition, flake graphite has a larger specific surface area and good adsorption properties. When the oxide or other light impurities in the copper liquid float to the surface, they will be adsorbed or captured by flake graphite, and these impurities will be removed with graphite later, so that the copper liquid can be purified. Further, the oxide and other non-metallic inclusions in the copper liquid are usually of lower density, and will float to the liquid surface under gravity. The presence of flake graphite can help these impurities to reach the surface of copper liquid more easily and be captured there. In addition, the graphite layer can also provide a stable interface so that these impurities will not be mixed into the copper liquid again.
[0045] In summary, the quality of chromium-zirconium-copper alloy can be improved by covering the surface of molten copper with flake graphite.
[0046] S4: Blowing argon gas (flow rate of 25-45 L / min) into the homogenization chamber and stirring the copper liquid to purify the copper liquid;
[0047] In this step, argon is a kind of inert gas, can not react chemically with the metal in copper liquid at high temperature to form a protective argon layer on the copper liquid surface, and this argon layer can effectively isolate the oxygen in the air to prevent the copper liquid from further oxidation. In addition, the argon gas blown into can produce bubbles in copper liquid, and these bubbles can drive copper liquid to flow when rising, and play the effect of stirring, and this stirring helps the impurities (such as oxides and other non-metallic inclusions) in copper liquid to float to the copper liquid surface, thereby being more easily removed. Meanwhile, by stirring, it is possible to further accelerate the impurities remaining in the copper liquid to float, so as to purify the copper liquid.
[0048] It should be noted that the reason why the argon flow rate is set between 25-45L / min is to ensure the best protection and stirring effect during the copper liquid treatment process. The appropriate argon flow rate can form a stable protective layer on the surface of the copper liquid, isolating the oxygen in the air and preventing the copper liquid from oxidizing. If the argon flow rate is too low (i.e. less than 25L / min), it may not be able to fully cover the surface of the copper liquid, causing some areas of the copper liquid surface to be exposed to the air and oxidized; on the contrary, if the flow rate is too high (i.e. greater than 45L / min), firstly, it will cause unnecessary waste, and secondly, excessive argon will cause the copper liquid to churn violently, causing the copper liquid to splash out, thereby affecting the stability of the smelting process.
[0049] S5: draining the purified copper liquid to an alloying crucible, and adding alloying elements chromium and zirconium to dissolve in the copper liquid;
[0050] In this step, first, the purified copper liquid is introduced into the alloying crucible through the drainage tube. The alloying crucible is divided into three chambers, including a wire feeding chamber, an overflow chamber, and a refining chamber. The purified copper liquid first flows into the wire feeding chamber. At this time, chromium core wire and CuZr are added to the wire feeding chamber. 50 Core wire, including chromium core wire and CuZr 50 The cored wire is added by a wire feeder and controlled by PLC. For every 100kg of electrolytic copper plate, 2 meters of chromium cored wire and 920mm of CuZr50 cored wire are added. At the same time, argon gas is continuously blown into the copper liquid and the copper liquid is continuously stirred, so that the alloy elements chromium and zirconium are uniformly dissolved in the copper liquid during the stirring process.
[0051] Secondly, the copper liquid containing chromium and zirconium is introduced from the wire feeding chamber into the overflow chamber to remove impurities generated during the process of adding the alloy elements chromium and zirconium, and the copper liquid containing chromium and zirconium after the impurities are removed is further sent to the refining chamber for refining to refine the chromium cored wire and CuZr 50 The impurities carried in the cored wire are further filtered to remove the remaining impurities, while allowing the alloying elements chromium and zirconium to be more evenly dissolved in the copper liquid.
[0052] After completing the above steps, the alloying crucible is opened, and the refined copper liquid dissolved with the alloy elements chromium and zirconium is introduced into a launder heated to 1280°C, and the copper liquid is further led into a crystallizer through the launder for casting. It should be noted that argon gas needs to be introduced during the process of flowing the copper liquid into the launder to ensure that the copper liquid is not oxidized.
[0053] It should be noted that the reason why chromium core wire and CuZr are added to the copper liquid is that 50 Core wire instead of other forms of chromium and CuZr 50Elements, the reason is: first, chromium core wire and CuZr 50 The cored wire is easier to disperse and dissolve in the copper liquid, which helps the alloy elements chromium and zirconium to be evenly distributed throughout the copper liquid. It is more efficient and controllable than directly adding pure metal blocks or powders. Second, chromium cored wire and CuZr 50 Core wire is usually made of a layer of copper covering the internal alloying elements (such as chromium or zirconium). This copper shell can protect the internal alloying elements from oxidation to a certain extent, thereby ensuring that these key alloying elements can be added to the copper liquid in a pure state.
[0054] S6: Casting and solidifying the copper liquid containing the alloy elements chromium and zirconium to obtain a chromium-zirconium-copper alloy.
[0055] In this step, the copper liquid in which the alloy elements chromium and zirconium are dissolved is cast and solidified. First, it is necessary to ensure that the temperature of the copper liquid is between 1280-1300°C (this temperature range can ensure that the copper liquid has good fluidity and low viscosity, so that it can flow smoothly into the crystallizer). Secondly, the copper liquid is drained to the crystallizer, and cooling water is introduced into the crystallizer so that the copper liquid is initially solidified to form a copper ingot; secondly, after the copper liquid is initially solidified in the crystallizer to form a copper ingot, the billet drawing machine is started to slowly pull the copper ingot downward at a speed of 30-50 mm / min to promote uniform solidification of the copper ingot; finally, cooling water is introduced into the crystallizer again and directly sprayed onto the surface of the copper ingot, and the chromium-zirconium-copper alloy can be obtained after complete cooling.
[0056] Furthermore, after obtaining the chromium-zirconium-copper alloy, the present embodiment further performs sawing operation on it. The specific operation process is as follows: when the chromium-zirconium-copper alloy is pulled downward by 3000 mm, the alloy is clamped with the jaws of the sawing machine and sawing is started. The feed speed of the saw blade is set to 15 mm / min. The whole sawing process lasts for about 13 minutes until the alloy is completely sawed off. After the alloy is sawed off, the sawn alloy is turned out of the casting pit by a blank turning machine for the next step of processing or transportation. After completing one sawing, the sawing machine rises and waits for the sawing work of the next process.
[0057] It should be noted that after obtaining the chromium-zirconium-copper alloy, the sawing operation is mainly performed on it to divide the alloy into suitable sizes and shapes for use in subsequent forging, rolling and other processing processes.
[0058] In another exemplary embodiment, the present application also provides a method for preparing a chromium-zirconium-copper alloy, comprising:
[0059] S10: preheating the electrolytic copper plate to 400°C for 45 minutes;
[0060] S20: melting the preheated electrolytic copper plate in a graphite crucible at a temperature of 1290° C. to obtain copper liquid;
[0061] S30: Covering the surface of the copper liquid with graphite flakes having a thickness of 100 mm, and draining the copper liquid covered with graphite flakes from the crucible to a homogenization chamber for 20 minutes;
[0062] S40: Blowing argon gas (flow rate 25-45 L / min) into the homogenization chamber and stirring the copper liquid to purify the copper liquid;
[0063] S50: draining the purified copper liquid to an alloying crucible, and adding alloying elements chromium and zirconium to dissolve in the copper liquid;
[0064] S60: Casting and solidifying the copper liquid containing the alloy elements chromium and zirconium to obtain a chromium-zirconium-copper alloy.
[0065] Different from the previous embodiment, the present embodiment directly injects chromium and zirconium elements into the copper liquid in the form of powder. The specific operation steps are as follows: first, the chromium powder and zirconium powder are evenly mixed in proportion; second, a suitable inert gas is selected as a carrier gas (argon is usually used because it does not chemically react with the copper liquid at high temperature and can effectively protect the copper liquid from oxidation); third, the mixed chromium and zirconium powders are evenly blown into the copper liquid through a carrier gas (such as argon). It should be noted that the flow rate of the carrier gas needs to be properly controlled, and it should not be too large to cause the copper liquid to churn violently, nor too small to cause the powder to be unable to be smoothly injected. At the same time, the copper liquid needs to be stirred during the injection process to ensure the rapid dissolution and uniform distribution of the powder in the copper liquid. The stirring can be achieved by mechanical stirring or by forming bubbles in the copper liquid through the carrier gas. Compared with the method of using chromium cored wire and CuZr50 cored wire, the present embodiment can improve the uniformity of the distribution of chromium powder and zirconium powder in the copper liquid through the method of powder injection, avoiding the local aggregation phenomenon that may occur in the traditional method; secondly, the fine powder has a larger surface area, which makes them dissolve faster in the copper liquid. Compared with large pieces of alloy materials, the powder is more easily absorbed and dissolved by the copper liquid, thereby shortening the dissolution time of the alloy elements in the copper liquid and improving the dissolution efficiency. In summary, the present embodiment can effectively improve the uniformity of the distribution and dissolution efficiency of chromium powder and zirconium powder in the copper liquid through the method of powder injection, thereby improving the overall performance of the chromium-zirconium-copper alloy including hardness, strength, wear resistance and corrosion resistance.
[0066] In another exemplary embodiment, the present application also provides a method for preparing a chromium-zirconium-copper alloy, comprising:
[0067] S100: preheat the electrolytic copper plate to 500°C for 60 minutes;
[0068] S200: melting the preheated electrolytic copper plate in a graphite crucible at a temperature of 1380° C. to obtain copper liquid;
[0069] S300: Covering the surface of the copper liquid with graphite flakes having a thickness of 150 mm, and draining the copper liquid covered with graphite flakes from the crucible to a homogenization chamber for 30 minutes;
[0070] S400: Blowing argon gas (flow rate 25-45 L / min) into the homogenization chamber and stirring the copper liquid to purify the copper liquid;
[0071] S500: draining the purified copper liquid to an alloying crucible, and adding alloying elements chromium and zirconium to dissolve in the copper liquid;
[0072] S600: Casting and solidifying the copper liquid containing the alloy elements chromium and zirconium to obtain a chromium-zirconium-copper alloy.
[0073] Compared with the above-mentioned embodiment, the improvement of this embodiment is that the chromium and zirconium elements are first mixed in a predetermined ratio, and then prepared into a powder alloy by ball milling or other processes. Then the prepared powder alloy is added to the copper liquid. Similarly, this embodiment also uses the pressure of the inert gas to send the powder alloy into the copper liquid.
[0074] Compared with powder injection, the chromium and zirconium elements are mixed in proportion before processing, and the consistency of the composition is ensured before adding the copper liquid. This can avoid local composition differences caused by uneven mixing during the addition process, thereby ensuring the uniformity of the final alloy material. In addition, since the chromium and zirconium elements have been pre-mixed, they can be dissolved and evenly distributed faster when added to the copper liquid, and no additional mixing time is required, which can further improve the production efficiency of chromium-zirconium-copper alloy.
[0075] In the above embodiment, the present application sets the preheating temperature of the electrolytic copper plate at 300°C to 500°C. Experiments have shown that within this temperature range, the oxides and other impurities on the surface of the electrolytic copper plate can be effectively decomposed, thereby reducing the entry of these impurities into the molten copper liquid, thereby improving the purity of the final product.
[0076] It should be noted that, according to experimental verification, if the preheating temperature is too high (i.e., greater than 500°C), first, it will cause local overheating of the electrolytic copper plate, or even overburning. Overburning will cause the surface quality of the electrolytic copper plate to deteriorate, and may even produce cracks or holes; second, it will cause the electrolytic copper plate to soften, or even bend, twist, and other deformations, which will not only affect the convenience of operation in subsequent processing steps, but may also affect the dimensional accuracy of the final product. In addition, if the preheating temperature is too low (i.e., less than 300°C), first, it will not be able to effectively decompose and remove oxides and other impurities on the surface of the electrolytic copper plate, which will cause these impurities to enter the copper liquid and affect the quality of the final alloy; second, the lower preheating temperature will cause the electrolytic copper plate to take longer to completely melt after entering the furnace, thereby reducing the smelting efficiency.
[0077] To sum up, preheating the electrolytic copper plate to 300°C to 500°C is the optimal choice made by this application after experimental verification. Under this temperature condition, it can not only effectively remove impurities on the surface of the copper plate, but also ensure that the copper plate will not be overburned and deformed due to excessively high temperature, and oxidation will be aggravated.
[0078] In the above embodiment, it has been verified by experiments that if the preheating time is less than 30 minutes, the electrolytic copper plate will be heated unevenly during the melting process, causing some areas to melt while other areas are still solid or semi-solid, resulting in the inability of chromium, zirconium and other elements to be completely dissolved and evenly distributed in the copper matrix, thereby affecting the performance of the chromium-zirconium-copper alloy. If the preheating time is greater than 60 minutes, the time the electrolytic copper plate is in contact with the air will increase, thereby increasing the risk of oxidation on the surface of the electrolytic copper plate.
[0079] In summary, the preheating time of 30-60 minutes is a time range that has been verified by experiments. Within this time range, it can ensure that the electrolytic copper plate reaches the ideal temperature state before melting, which helps to reduce the temperature difference generated during the melting process, thereby reducing thermal stress, and then ensuring the uniformity of the chromium-zirconium-copper alloy composition and reducing the risk of cracks in the chromium-zirconium-copper alloy.
[0080] In the above embodiment, the present application melts the preheated electrolytic copper plate in a graphite crucible at 1200°C to 1380°C. This temperature range is selected through experimental optimization to ensure the effective melting of the preheated electrolytic copper plate and the uniform dissolution of subsequent alloying elements. Specifically, the melting point of copper is about 1085°C, while the melting points of chromium and zirconium are 1890°C and 1855°C, respectively. Within the temperature range of 1200°C to 1380°C, it can be ensured that the copper is completely melted, and sufficient heat is provided for the chromium and zirconium to be added so that they can be evenly dissolved in the copper liquid. In addition, this temperature range also helps the oxides and other impurities in the copper liquid to float, which is convenient for removal, thereby improving the purity of the alloy.
[0081] It should be noted that if the temperature is too high (i.e. greater than 1380°C), some elements in the copper liquid will evaporate, especially some volatile trace elements, which will affect the composition consistency of the alloy; in addition, although a protective atmosphere (such as argon) is used during the melting process, excessively high temperatures may still lead to intensified oxidation of the copper liquid surface, thereby producing more oxide impurities. In addition, if the temperature is too low (i.e. less than 1200°C), firstly, the electrolytic copper plate will not be completely melted, resulting in uneven smelting and affecting the quality of the final product; secondly, the lower temperature is not enough to completely dissolve the alloy elements in the chromium and zirconium cored wires into the copper liquid, resulting in uneven alloy composition; thirdly, under low temperature conditions, the viscosity of the copper liquid is high and the fluidity is poor, which makes it difficult for impurities and oxide particles inside the copper liquid to move to the surface of the copper liquid, and therefore difficult to be effectively removed; in addition, during the melting process, argon and other inert gases are usually introduced into the copper liquid to stir the copper liquid and promote the floating of impurities. However, under low temperature conditions, the solubility of inert gases such as argon in the copper liquid increases, and the number of bubbles formed decreases, resulting in a weakened stirring effect, which in turn affects the floating of impurities.
[0082] In the above embodiment, the present application controls the thickness of the flake graphite between 50-150mm, because: if the thickness of the flake graphite is less than 50mm, the thickness of the flake graphite will be too thin. The too thin flake graphite cannot effectively isolate the oxygen in the air, which will make the copper liquid prone to oxidation reaction, thereby reducing the purity of the copper liquid; second, it is difficult to form a stable isolation barrier, which will cause the oxides and other light impurities on the surface of the copper liquid to be unable to be effectively captured and removed; third, the thermal insulation performance provided is insufficient, which will cause the surface of the copper liquid to dissipate heat quickly, which is not conducive to maintaining the temperature stability during the smelting process; fourth, if the graphite layer is too thin, it cannot completely cover the entire copper liquid surface, which will cause some areas of the copper liquid to be exposed to the air, causing these areas to be prone to oxidation. In addition, if the thickness of the flake graphite is greater than 150mm, first, it will slow down the heat transfer, affect the uniformity of the temperature in the furnace, and thus affect the melting and refining process of the copper liquid; second, too much graphite may be mixed into the copper liquid when removed, and instead become a new source of impurities.
[0083] In summary, the present application controls the coverage thickness of flake graphite between 50-150mm, which is the result of multiple considerations such as protecting the copper liquid from oxidation, improving the efficiency of impurity removal, ensuring good heat transfer performance and maintaining reasonable production costs, and this result is obtained after experimental verification.
[0084] In the above embodiment, if the holding time of the copper liquid is less than 10 minutes, the holding time is too short, resulting in insufficient time for the added elements such as chromium and zirconium to completely mix with the copper matrix, thereby causing uneven composition of the chromium-zirconium-copper alloy, which in turn affects the subsequent casting and casting process. If the holding time of the copper liquid is greater than 30 minutes, the holding time is too long, which increases the risk of trace oxygen entering and causes oxidation of the copper liquid surface.
[0085] In summary, the present application sets the insulation time within 10-30 minutes, which can ensure that the chromium and zirconium elements can be fully mixed with the copper matrix and ensure that the composition of the chromium-zirconium-copper alloy is uniform, and can reduce the risk of oxidation of the copper liquid.
[0086] Figure 2 is a schematic diagram of the macroscopic metallographic structure of the chromium-zirconium-copper alloy prepared in this application, Figure 2 It can be seen that the chromium-zirconium-copper alloy produced by casting by this method has fine and uniform grain structure on a macro scale, and is free of casting defects such as cracks, inclusions, segregation, and pores. This shows that the steps of preheating, melting, purification, and homogenization in the preparation process effectively control the alloy composition, and the casting process ensures the consistency and integrity of the material.
[0087] Figure 3 is a schematic diagram of the microstructure of the chromium-zirconium-copper alloy prepared in this application, consisting of Figure 3 It can be seen that the chromium-zirconium-copper alloy produced by casting by this method has a fine and uniformly distributed grain structure, which indicates that an effective grain refinement process was adopted during the preparation process. Figure 3 No obvious casting defects such as cracks or inclusions were found, indicating that the successful implementation of the preheating, melting, purification and homogenization steps ensured the high uniformity of the chromium-zirconium-copper alloy composition. Such a microstructure is conducive to improving the various properties of the chromium-zirconium-copper alloy.
[0088] Figure 4 is a schematic diagram of electron microscope scanning of the chromium-zirconium-copper alloy prepared in this application, Figure 4 A higher resolution image is given by Figure 4 It can be seen that the boundaries between the grains in the chromium-zirconium-copper alloy are very clear, and the clear grain boundaries indicate that the crystal growth is well controlled during the casting and cooling process. This means that the atoms in the melt are arranged in an orderly manner to form a clear grain structure, without excessive supercooling or abnormal grain boundary formation caused by uneven cooling (if there are defects or unevenness in the grain boundaries, it is easy to become the starting point for crack initiation and expansion, reducing the toughness and ductility of the chromium-zirconium-copper alloy), thereby ensuring that the various properties of the chromium-zirconium-copper alloy are optimized.
[0089] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A chromium-zirconium-copper alloy, characterized in that: The components of the chromium-zirconium-copper alloy and the content of each component include: Chromium (Cr): 0.5-1.5% Zirconium (Zr): 0.02-0.2% Copper (Cu): balance.
2. A method for preparing a chromium-zirconium-copper alloy, characterized in that: The method comprises: Preheating the electrolytic copper plate; Melting the preheated electrolytic copper plate to obtain copper liquid; The surface of the molten copper is covered with graphite flakes to keep the molten copper warm; Purifying the copper liquid after heat preservation; The alloying elements chromium and zirconium are dissolved in the purified copper solution; The copper liquid in which the alloy elements chromium and zirconium are dissolved is cast and solidified to obtain a chromium-zirconium-copper alloy.
3. The preparation method according to claim 2, characterized in that: The preheating temperature is 300-500°C.
4. The preparation method according to claim 2, characterized in that: The preheating time is 30-60 minutes.
5. The preparation method according to claim 2, characterized in that: The melting temperature of the electrolytic copper plate is 1200-1380°C.
6. The preparation method according to claim 2, characterized in that: The covering thickness of the flake graphite is 50-150 mm.
7. The preparation method according to claim 2, characterized in that: The copper liquid is kept warm for 10-30 minutes.
8. The preparation method according to claim 2, characterized in that: During the purification of the copper liquid after heat preservation, argon gas needs to be blown into the surface of the copper liquid, and the flow rate of the argon gas is 25-45 L / min.
9. The preparation method according to claim 2, characterized in that: The casting temperature of the copper liquid in which the alloy elements chromium and zirconium are dissolved is 1280-1300°C.
10. An alloying crucible, characterized in that: The alloying crucible comprises a wire feeding chamber, an overflow chamber and a refining chamber, wherein: The wire feeding chamber is used for adding and dissolving the alloying elements chromium and zirconium; The overflow chamber is used to remove impurities generated during the process of adding alloying elements chromium and zirconium; The refining chamber is used for refining the copper liquid to which the alloy elements chromium and zirconium are added.